GLOCAL BALANCING: INSERTING INDONESIAN CULTURAL CONTENT INTO ENGLISH TEXTBOOK FOR GRADE X - I Gusti Ayu Diah Gita Saraswati; Ni Komang Arie Suwastini; Putu Suarcaya (PRASI, 2023)
While learning English as a Foreign language implies learning the culture of its native speaker, the Indonesian Ministry of Education and Culture mandated that the Indonesian culture be preserved and cultivated. Preserving and cultivating values is best done through literacy conveyed via text in the classroom. Concerning preserving and cultivating Indonesian values, the present study analyzed an English Textbook for Indonesian students in Grade X. The study was conducted as a descriptive qualitative research. Data collected from the source was analyzed using the concept of culture by Byram & Morgan. The findings show that the textbook contains a representation of local Indonesian culture in the form of social identities and social groups, beliefs and behavior, socio-political institutions, socialization and the life-cycle, national cultural heritage, and national geography that represent Indonesia as a prosperous nation with fertile lands and rich natural resources. The book also represents social interactions, national history, stereotypes, and national identity as a developing nation since Indonesia's independence from colonialization. With the abundant representations of local Indonesian culture, the English textbook supports the preservation of the local culture amidst the introduction of the foreign culture brought by the introduction of English as the target language and target culture, promoting a balance of global-local combination that can reap benefits from the best of both cultures.